1995
DOI: 10.1021/bi00030a002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a D-Amino Acid Aminotransferase: How the Protein Controls Stereoselectivity

Abstract: The three-dimensional structure of D-amino acid aminotransferase (D-AAT) in the pyridoxamine phosphate form has been determined crystallographically. The fold of this pyridoxal phosphate (PLP)-containing enzyme is completely different from those of any of the other enzymes that utilize PLP as part of their mechanism and whose structures are known. However, there are some striking similarities between the active sites of D-AAT and the corresponding enzyme that transaminates L-amino acids, L-aspartate aminotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
154
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(158 citation statements)
references
References 29 publications
4
154
0
Order By: Relevance
“…If Lys337 proves not to be part of the SAM binding domain, it may form an internal aldimine with PLP, which may be displaced by the substrate during catalysis. Such a mechanism has been reported for PLP-dependent amino acid aminotransferases (41). It has also been reported that a glycine-rich conserved region (GXXGXXGG) has been found in all known aminolevulinate synthases, glycogen phosphorylase b, and tryptophan synthase (17,21,29).…”
Section: Discussionmentioning
confidence: 54%
“…If Lys337 proves not to be part of the SAM binding domain, it may form an internal aldimine with PLP, which may be displaced by the substrate during catalysis. Such a mechanism has been reported for PLP-dependent amino acid aminotransferases (41). It has also been reported that a glycine-rich conserved region (GXXGXXGG) has been found in all known aminolevulinate synthases, glycogen phosphorylase b, and tryptophan synthase (17,21,29).…”
Section: Discussionmentioning
confidence: 54%
“…It is, therefore, crucial for the enzyme to have a correct arrangement of the active site groups in order to accumulate E-Q. Although the stereospecificity of D-AAT is opposite to that of aspartate aminotransferase, crystallographic data revealed that the arrangement of the active site groups is quite similar (Sugio et al, 1995). The fact that the reaction of D-AAT with D-serine and erythro-β-hydroxy-DL-aspartate results in the accumulation of E-Q as a major peak, but the reaction of Dthreonine that has a threo β-hydroxy group could not, suggests the requirement of a certain structural arrangement of the active site groups for the accumulation of E-Q (Martinez del Pozo et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…aspartate aminotransferase [5], o-amino acid:pyruvate aminotransferase [6], tyrosine phenol-lyase [7], and dialkylglycine decarboxylase [8], belong to the a-family and resemble each other very strongly in their three-dimensional structures [9]. o-Amino acid aminotransferase, which is only very distantly related to the members of the a-family, has a structural organisation completely different from those of any of the enzymes that utilize PLP [10]. Furthermore, the fl-subunit of tryptophan synthase, which catalyzes the PLP-dependent part of the reaction, is a member of the fl-family and has a tertiary structure [11] that bears no resemblance to that of the enzymes of the a-family.…”
Section: Introductionmentioning
confidence: 99%